Shine your light: The life and lessons of Madeline Woleg - Sunderland, Naomi; Graham, Phil; Spence, Joel; Cooper, Rae; Harris, Kayla (Self published electronic and paperback peer reviewed community requested output, 2021)
Research background: This research seeks to understand the ways in which First Nations People use music as a means of advocacy. The research builds on three years of arts based community development activity in Vanuatu with local musicians and cultural leaders. The research was funded by the Queensland Conservatorium Research Centre and an Academic Studies Program grant from Griffith Health and the University of the Sunshine Coast. The project was titled Songs of Self Determination and involves musicians from Australia and Vanuatu. A key aim was to collect musicians' and song writers' accounts of how musical performance and distribution promotes self-determination, health, and human rights for First Nations' Peoples in Australia and Vanuatu. Research contribution: This research spans Indigenous studies, performing and creative arts, and social work fields of study. The study and related outputs provides a contemporary understanding of how diverse First Nations musicians and song writers practice self-advocacy and assertion that in turn shapes powerful social and environmental determinants of health for their communities. Research activities included in depth interviews and storytelling with First Nations songwriters and musicians in Australia and Vanuatu and group songwriting on topics that were important to community members. Research significance: This is a community requested output from research. First Nations health is an international priority. Existing literature demands strengths based and culturally safe forms of health promotion and research with First Nations Peoples internationally. This research offered all of those things through privileging and investigating the role of cultural and musical self-determination and self-advocacy in shaping known social and environmental determinants of health. The community and academic outputs from the project document both First Nations voice and the impact of their sovereign musical and cultural activity. No Full Text